IMPROVING THE SERVICE SECTOR IN THE CONTEXT OF THE DEVELOPMENT OF THE DIGITAL ECONOMY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Today, the most important issue in Uzbekistan is to increase the volume of foreign investment in the country's economy through the development of the digital economy and the creation of a favorable investment climate. Therefore, this article analyzes the development of the digital economy in Uzbekistan and the prospects for creating a favorable investment climate based on the development of the digital economy. In addition, the volume of foreign investment in Uzbekistan has been analyzed and proposals have been made to create a favorable investment climate based on the development of the digital economy.